Development of contingency cost analysis model in construction project with cost-time-quality risk integration - Astana, I Nyoman Yudha; Sudarsana, Dewa Ketut; Frederika, Ariany; Sanjaya, Putu Ari (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the contingency cost in the implementation of construction projects. The problem to be solved is the develop a contingency cost model in the implementation of construction projects, by integrating cost, quality, and time risks. The previously used models involve cost, quality, and time risks separately. It is still rare to find an analysis in construction project execution that incorporates these three risks into a contingency cost model. The formulation of this integration is crucial since every project is unique and carries varying degrees of risk. Data were investigated and collected from the Bali Province Regency Road Improvement Project, and the descriptive strategy analysis was employed. Using the probability (P) by impact (I) approach, which is the multiplication of (P) by (I) on a Likert scale of 5, triple constraint risks are included in the Expected Monetary Value (EMV) analysis. Moreover, monetary units are used to develop impact scale I, in which daily penalties and quality with rework costs are applied using the monetary unit approach of time effect. The simultaneous total of the PI from time, cost, and quality concerns is the EMV contingency cost formulation for the integration of these risks. The study obtained that, a cost contingency model was created that incorporates the risk factors of cost, time, and quality. This model’s cost contingency value was 9.61% of the total cost when it was applied to a case study. Specifically, this finding falls between 5% and 10%, which is adequate and consistent with the empirical approach. This contingency cost model is thought to be more rational since it accounts for project risks, including the likelihood of potential risks as well as their effects. The project team can use this approach to estimate contingency expenses